Investigating interfacial electron transfer in dye-sensitized NiO using vibrational spectroscopy - Black, Fiona A.; Clark, Charlotte A.; Summers, Gareth H.; Clark, Ian P.; Towrie, Michael; Penfold, Thomas J.; George, Michael W.; Gibson, Elizabeth A. (Royal Society of Chemistry, 2017)
Understanding what influences the formation and lifetime of charge-separated states is key to developing photoelectrochemical devices. This paper describes the use of time-resolved infrared absorption spectroscopy (TRIR) to determine the structure and lifetime of the intermediates formed on photoexcitation of two organic donor–π–acceptor dyes adsorbed to the surface of NiO. The donor and π-linker of both dyes is triphenylamine and thiophene but the acceptors differ, maleonitrile (1) and bodipy (2). Despite their structural similarities, dye 1 outperforms 2 significantly in devices. Strong transient bands in the fingerprint region (1 and 2) and nitrile region (2300–2000 cm−1) for 1 enabled us to monitor the structure of the excited states in solution or adsorbed on NiO (in the absence and presence of electrolyte) and the corresponding kinetics, which are on a ps–ns timescale. The results are consistent with rapid (<1 ps) charge-transfer from NiO to the excited dye (1) to give exclusively the charge-separated state on the timescale of our measurements. Conversely, the TRIR experiments revealed that multiple species are present shortly after excitation of the bodipy chromophore in 2, which is electronically decoupled from the thiophene linker. In solution, excitation first populates the bodipy singlet excited state, followed by charge transfer from the triphenylamine to the bodipy. The presence and short lifetime (τ ≈ 30 ps) of the charge-transfer excited state when 2 is adsorbed on NiO (2|NiO) suggests that charge separation is slower and/or less efficient in 2|NiO than in 1|NiO. This is consistent with the difference in performance between the two dyes in dye-sensitized solar cells and photoelectrochemical water splitting devices. Compared to n-type materials such as TiO2, less is understood regarding electron transfer between dyes and p-type metal oxides such as NiO, but it is evident that fast charge-recombination presents a limit to the performance of photocathodes. This is also a major challenge to photocatalytic systems based on a “Z-scheme”, where the catalysis takes place on a µs–s timescale.